Exploring the Impact of Perceived Usefulness and Enjoyment to Enhance Intention to Use and Satisfaction among Metaverse Travellers - Amron, Amron; Mursid, Ali; Suhartono, Entot (Journal of Ecohumanism, 2024)
Orientation: This study explored metaverse travelers focusing on the platform of Worderverse Indonesia to enhance the intention to use and satisfaction. Purpose of the study: First, this study verifies the influence of metaverse travellers’ perceived usefulness on metaverse travellers' intention to use and satisfaction. Moreover, it investigates the impact of the metaverse travellers’ perceived enjoyment on metaverse travellers’ intention to use and satisfaction. Finally, this framework explores the influence of metaverse travellers’ intention to use on metaverse travellers' satisfaction. Research approach/design and method: Employing a simple random sampling method, the sample of this study includes 183 metaverse travellers who use the platform Wondersverse Indonesia. This study analysed the data employing confirmatory factor analysis and structural equation modelling via Amos program. Main Findings: The results showed that metaverse travellers’ perceived usefulness positively and significantly impacts metaverse travellers’ intention to use and satisfaction. Similarly, metaverse travellers’ perceived enjoyment positively and substantially affects metaverse travelers’s intention to use and satisfaction. Finally, metaverse travellers' intention to use positively and significantly affects metarverse travellers’ satisfaction. Practical/managerial implications: The research findings afford significant understandings into management implications for enhancing metaverse platforms like Wondersverse Indonesia. Orientation: This study explored metaverse travelers focusing on the platform of Worderverse Indonesia to enhance the intention to use and satisfaction.